THE STUDY OF TEACHING AND LEARNING DEBATE AT FOURTH SEMESTER OF ENGLISH DEPARTMENT UNISMA - Intan Widiya Safitri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstractThis study aimed at investigating the activities existed in the pre, whilst, post activity, assessment and students’ opinion upon the use of debate in the class. The respondents of this study were fourth semester students of English Department UNISMA allocated in class A. The data were analyzed in the form of descriptive qualitative analysis using data reduction, display data and drawing conclusion by narrating the information taken from classroom observation checklist, interview sheet for lecturer, interview sheet for student and lecturer’s document. Dealing with the implementation of Asian Parliamentary Debate, the findings of this study is executed. Including from pre-activity, the teacher taught the students based on the RPS provided and students did the right direction as lecturer’ utterance. In whilst activity, teaching and learning debate run well due to subject matter has been mastered and practiced even though there were several students could not deliver the arguments well. In post activity, the comment session has been delivered well either from the lecturer or two adjudicators as the representative from students. From the assessment sides, the lecturer categorized students’ debate performance based on pronunciation, content and argument. Furthermore, it is also being supported by students’ opinion upon the use of debate in the class; most of them have the same opinion that debate is one of challenging activity which can boost them to develop their critical thinking and oral communication ability. Keywords: teaching and learning, debate implementation, speaking